Variation in Language : Code switching in Czech as a challenge for sociolinguistics. - Sgall, Petr (Linguistic & literary studies in Eastern Europe ;, 1992)
Czech, a clear case of a language having a Standard and a strong central vernacular with intensive shifting between them, offers many points of general interest to sociolinguists. This volume is divided in 5 chapters and opens with a general discussion of language varieties. 'The Two Central Language Formations in Czech' gives a summary description of the Czech central vernacular. This is followed by a chapter on 'The Origin and Opposition of Standard and Common Czech' and in the next chapter code switching between Standard and Common Czech is discussed. The concluding chapter presents startin.